Perception of clothing styles among selected pre-school teachers - Santos, Anna Patricia C. (College of Home Economics. University of the Philippines Diliman, 2013)
ABSTRACT As a non-verbal form of communication, clothing functions as an indicator of one's personal and social identity. This research focuses on pre-school teacher ensembles and the perceptions of teachers-in-training, pre-school teachers, and parents in terms of its conformity to the image of an effective pre-school teacher. Sixty respondents participated in the survey to answer questions relating to a photo of a male and a female subject dressed in the commonly worn ensembles by pre-school teachers, as observed by the researcher. Twenty respondents were informed that the subjects on the photos were pre-school teachers, while forty respondents were asked to identify their professions. Based on the results, character description is easier to form on female ensembles than male ensembles. When the subjects were identified as a preschool teacher, the collared shirt male ensemble, and the plain shirt female ensemble, were the most positively received. When the subjects' occupations were open to interpretation, the cardigan female ensemble was the most positively received. These findings will assist teachers-in-training and pre-school teachers in determining the ensembles they wear in class in terms of how they want to be perceived. Male preschool teachers are perceived as more effective when wearing casual, slim-fitting ensembles; and female preschool teachers are perceived as more effective when wearing casual, loose-fitting ensembles. With these findings, this study was able to show how teacher ensembles can be used as forms of non-verbal communication to reflect one's character, which can be used guide preschool teachers in impression management and improve their interaction among peers and parents.